Labrumoides vibrissa (Arthropoda: Pycnogonida), new callipallenid genus and new species from north Western Australia - Staples, David A. (Zootaxa, 2020)
Specimens housed in the Australian Museum assigned to the genus Stylopallene are reviewed on the basis of their questionable geographic locations in the tropical waters of north Western Australia. Re-examination of those specimens shows only a superficial resemblance to the genus Stylopallene. The new genus Labrumoides gen. nov. is erected to accommodate those specimens and a new species L. vibrissa sp. nov. is described. Cheilopallene hirta previously assigned to genus incertae sedis is provisionally reassigned to the new genus.